COPYRIGHT ISSUE ON MUSIC BACK SOUND USAGE ON YOUTUBE VIDEO - Idha Pratiwi Dyah Sinta Dewi; Ravina Savitri; Alifah Nur Fitriana Naridha; Normalita Destyarini (Fakultas Hukum, Universitas Diponegoro, 2022)
The emergence of social media Youtube also raises new legal problems in the field of copyright. The use of music as a video background by a content creator is often done without the permission of the creator. Using the work without the author's permission violates the exclusive rights of the creator. This paper will describe the policies that YouTube has in protecting music creators as well as law enforcement efforts for Content Creators who use music as a background without the creator's permission in connection with copyright regulations in Indonesia. The research is normative research using a statutory approach, data collection through library research, and analysis using descriptive-analytical techniques. The results of the study show that the protection of music as a background for videos uploaded on the Youtube site is regulated in Article 5, Article 9, and Article 20 of the Copyright Law. Copyright legal protection is provided by Youtube by granting a license, through this license copyright holders can claim Content ID in the event of a violation of copyrighted material. The Indonesian government provides repressive measures that can be taken in the event of copyright infringement through litigation and non-litigation.